Inhibition of Fucosylation in Human Invasive Ductal Carcinoma Reduces E-Selectin Ligand Expression, Cell Proliferation, and ERK1/2 and p38 MAPK Activation - Carrascal, M (2018)
Breast cancer tissue overexpresses fucosylated glycans, such as sialyl-Lewis X/A (sLeX/A ), and α-1,3/4-fucosyltransferases (FUTs) in relation to increased disease progression and metastasis. These glycans in tumor circulating cells mediate binding to vascular E-selectin, initiating tumor extravasation. However, their role in breast carcinogenesis is still unknown. Here, we aimed to define the contribution of the fucosylated structures, including sLeX/A , to cell adhesion, cell signaling, and cell proliferation in invasive ductal carcinomas (IDC), the most frequent type of breast cancer. We first analyzed expression of E-selectin ligands in IDC tissue and established primary cell cultures from the tissue. We observed strong reactivity with E-selectin and anti-sLeX/A antibodies in both IDC tissue and cell lines, and expression of α-1,3/4 FUTs FUT4, FUT5, FUT6, FUT10, and FUT11. To further assess the role of fucosylation in IDC biology, we immortalized a primary IDC cell line with human telomerase reverse transcriptase to create the 'CF1_T cell line'. Treatment with 2-fluorofucose (2-FF), a fucosylation inhibitor, completely abrogated its sLeX/A expression and dramatically reduced adherence of CF1_T cells to E-selectin under hemodynamic flow conditions. In addition, 2-FF-treated CF1_T cells showed a reduced migratory ability, as well as decreased cell proliferation rate. Notably, 2-FF treatment lowered the growth factor expression of CF1_T cells, prominently for FGF2, vascular endothelial growth factor, and transforming growth factor beta, and negatively affected activation of signal-regulating protein kinases 1 and 2 and p38 mitogen-activated protein kinase signaling pathways. These data indicate that fucosylation licenses several malignant features of IDC, such as cell adhesion, migration, proliferation, and growth factor expression, contributing to tumor progression.